Après Coup: Retroactive Memory: A Conversation with Jean-Bertrand Pontalis - Sergio Benvenuto (EJP import test, 2019)
This conversation between Sergio Benvenuto and Jean-Bertrand Pontalis took place on 13 October 1989 in the latter’s office at Éditions Gallimard in Paris.
Keywords: Après coup; Freud & Lacan; Hic et nunc; historicity; Memory and rememoration